A lei 13.123/15 enquanto mecanismo de tutela da biodiversidade brasileira e o Protocolo de Nagoia - Gössling, Luciana Manica (2016)
The Convention on Biological Diversity, designed in 1992, was intended to protect the conservation and sustainable use of biological diversity and the equitable fair distribution of benefits from the utilization of genetic resources ( English term, "ABS"). The third objective remains not sufficiently cleared and the countries felt the need to legislate on the subject before the eminent importance of the rights arising from the exploitation of genetic resources and traditional knowledge associated with them and the transboundary damage from predatory exploitation. Countries faced with a growing biodiversity degradation in an uncontrolled and a reduction of fauna and flora form. They start question the exploratory use and necessary preservation of sociobiodiversity for future generations based on interculturalism, and the effect of such rights in social harvest, cultural, political and economic. To address such conflicts on the international scene came the Nagoya Protocol, and in Brazil, Law 13.123/ 2015. Both laws walked in the same direction, with flexible access to traditional knowledge and biodiversity, striving for expansion of research and innovation. The literature search was performed using the deductive method, lying on the theme Rights Research Line Sociobiodiversity and Sustainability. The Nagoya Protocol left the national legislation up to each country, bringing minimum dictates. Brazil has not ratified but implemented specific legislation that included the protection of genetic resources and associated traditional knowledge, however, gave way to exploratory mean.